Early lymphocyte levels and low doses radiation exposure of lung predict lymphopenia in radiotherapy for lung cancer - Kuncman, Łukasz; Pajdziński, Matusz; Smółka, Krzysztof; Bilski, Mateusz; Socha, Joanna; Stando, Rafał; Peszyńska-Piorun, Magdalena; Korab, Katarzyna; Jereczek-Fossa, Barbara Alicja; Fijuth, Jacek (Frontiers in Immunology, 2024)
Radiation induced lymphopenia (RIL) deteriorate survival and diminishes the benefit of immune checkpoint inhibitors in combined treatment of lung cancer. Given the inconsistent data across various studies on the predictors of RIL, we aim to methodically elucidate these predictors and formulate a practical guide for clinicians.We conducted observational cohort study in four tertiary cancer centers. Patients with non-small cell lung cancer and small cell lung cancer, without lymphopenia grade >1, who underwent standalone radiotherapy (RT) in minimum 15 fractions were eligible. Dose-volume parameters of structures and clinical factors were comprehensively analyzed using various predictors selection methods and statistical models (Linear Regressors, Elastic Net, Bayesian Regressors, Huber Regression, regression based on k-nearest neighbors, Gaussian Process Regressor, Decision Tree Regressor, Random Forest Regressor, and eXtreme Gradient Boosting, Automated Machine Learning) and were ranked to predict lymphocytes count nadir (alc_nadir).Two hundred thirty eight patients (stage I-3.4%, II-17.6%, III-75.2%, IV-3.8%) who underwent RT to median dose of 60 Gy were analyzed. Median alc_nadir was 0.68K/mm 3 . The 60 feature sets were evaluated in 600 models (RMSE 0.27-0.41K/mm³). The most important features were baseline lymphocyte count (alc_1), mean lung_dose, lung v05, lung v10, heart v05 and effective dose to immune cells (edic). In patients with alc_1 ≤ 2.005K/mm 3 , median alc_nadir predictions were 0.54K/mm 3 for lung_v05p > 51.8% and 0.76K/mm 3 for lung_v05p ≤ 51.8%. Lymphopenia was rare in patients with alc_1 > 2.005K/mm 3 . RIL was most severe in patients with low early lymphocyte counts, primarily triggered by low RT doses in the heart and lungs.